Notice of Removal: Automated super-resolution image processing in ultrasound using machine learning - Jeffries,KC; Schirmer,M; Brown,J; Harput,S; Tang,MX; Dunsby,C; Aljabar,P; Eckersley,R (2017)
Clinical implementation of super-resolution (SR) ultrasound imaging requires accurate single microbubble detection, and would benefit greatly from automation in order to minimize time requirements and user dependence. We present a machine learning based post-processing tool for the application of SR ultrasound imaging, where we utilize superpixelation and support vector machines (SVMs) for foreground detection and signal differentiation.